Nutritional evaluation of house cricket (Brachytrupes portentosus) meal for poultry - Abdul Razak, Ismasyahir; Ahmad, Yusof Hamali; Engku Ahmed, Engku Azahan (2012)
This study was conducted to evaluate the nutritional value of house cricket meal (HCM) as an alternative feedstuff for poultry. The proximate chemical composition, amino acid (AA) content and total metabolisable energy (TME) of HCM were determined. The protein quality of HCM was evaluated using protein efficiency ratio (PER) and net protein ration (NPR) methods. Treatment diets consisted of basal diet (N-free), basal + HCM, basal + soy bean meal (SBM) and basal + fish meal (FM) and were arranged in a completely randomized design. The crude protein (CP) content of HCM was 60.4% and the value was higher than that of either SBM or FM. Total metabolisable energy value for HCM was similar to that of corn but was much lower than that of SBM. Total amount of tryptophan, tyrosine and valine in the HCM were 2.8, 2.4 and 3.2%, respectively. These values were higher than those in SBM and FM. The percentages of lysine, methionine and cysteine in HCM were 2.4, 0.5 and 0.8%, respectively. These values were similar to those in SBM (2.9, 0.6 and 0.7%) but lower than FM (4.5, 1.7 and 0.8%). Chicks fed HCM diet recorded higher (p<0.05) weight gain than chicks fed SBM but slightly lower than chicks fed FM. The PER values for HCM, SBM and FM were 3.42, 3.11 and 3.71, respectively. NPR values for HCM, SBM and FM were 3.66, 3.29 and 3.96, respectively. The PER and NPR values of HCM were higher (p<0.05) than that of SBM but slightly lower than that of FM. The results suggest that the HCM has a substantial amount of protein and energy which could to be included in poultry diets.